A INTERNACIONALIZAÇÃO DO ENSINO SUPERIOR NO BRASIL: UMA PROPOSTA DE MATRIZ MULTIDIMENSIONAL DE (AUTO) AVALIAÇÃO - Amorim, Gabriel Brito (2020)
The internationalization of higher education, understood as the process of integrating an international, intercultural or global dimension in the teaching, research and outreach services of higher education (KNIGHT, 2003) has been a central the